2022
DOI: 10.3390/molecules27103132
|View full text |Cite
|
Sign up to set email alerts
|

Green and Efficient Extraction of Polysaccharide and Ginsenoside from American Ginseng (Panax quinquefolius L.) by Deep Eutectic Solvent Extraction and Aqueous Two-Phase System

Abstract: In this study, a green and effective extraction method was proposed to extract two main compounds, ginsenosides and polysaccharides, from American ginseng by combining deep eutectic solvents (DESs) with aqueous two-phase systems. The factors of type of DESs, water content in DESs, the solid–liquid ratio, extraction temperature, and extraction time were studied in the solid–liquid extraction. Then, the aqueous two-phase system (DESs-ethylene oxide–propylene oxide (EOPO)) and salty solution exchange (EOPO-salty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…197 They are the most prevalent natural macromolecular polymers and can be differentiated based on specic monosaccharide units, chain length, and branching. These compounds play a crucial role as natural bioactive components in food matrices owing to their well-established antioxidant, anticancer, antiviral, antibacterial, probiotic, prebiotic, relatively low cytotoxic, and healthpromoting properties, 198,199 supporting their applications in food matrices. Naturally occurring polysaccharides exhibit diversity in their structural, functional, conformational, and biological characteristics.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…197 They are the most prevalent natural macromolecular polymers and can be differentiated based on specic monosaccharide units, chain length, and branching. These compounds play a crucial role as natural bioactive components in food matrices owing to their well-established antioxidant, anticancer, antiviral, antibacterial, probiotic, prebiotic, relatively low cytotoxic, and healthpromoting properties, 198,199 supporting their applications in food matrices. Naturally occurring polysaccharides exhibit diversity in their structural, functional, conformational, and biological characteristics.…”
Section: Polysaccharidesmentioning
confidence: 99%
“…The extraction of these groups of compounds from the plant material can be effectively carried out with DESs based on choline chloride as the HBA, summarized in Table . , …”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%
“…AG has a long history of use and is widely distributed in China, and its components and contents may differ slightly due to varying growth environments [15][16][17]. To date, various compounds including ginsenosides, polysaccharides, flavonoids, fatty acids, polyalkynes, volatile oils, amino acids, carbohydrates, vitamins, and trace elements have been isolated from AG, and ginsenosides and polysaccharides are widely acknowledged as the primary active constituents [18,19]. Studies have demonstrated that ginsenosides possess hypoglycemic [20], anti-tumor [21], cardioprotective [22] and neuroprotective properties [23]; they can also inhibit aging processes as well as improve sleep quality and learning and memory impairments [24].…”
Section: Introductionmentioning
confidence: 99%